Electro-polymerization of modified carbon paste sensor for detecting azithromycin - Salma Mamdouh; M. Shehata; A. M. Fekry; M. A. Ameer (Scientific Reports)
Abstract Azithromycin (AM) is one of the prescribed drugs in pandemic medication treatment which has paid great attention. We developed in this study a simply modified carbon paste electrode (CPE) to detect AM using poly-threonine (PT). PT or similar polymers are used as carriers to enhance the delivery and effectiveness of AM. The work was characterised via Cyclic Voltammetry (CV), electrochemical impedance spectroscopy (EIS) and scanning electron microscopy (SEM). We take into consideration the effects of pH, scan rate, accumulation time, interference, and calibration curve.A very sensitive response to the oxidation of 1.0 mM from AM in phosphate buffer solution (PBS) over a pH range of 5.0 to 10.0 was observed using the developed poly-threonine carbon paste electrode (PTCPE). The impact of different AM concentrations was investigated resulting in a detection limit of 0.32 µM and a quantification limit of 1.07 µM at PBS (pH 7.4). Finally, the recently used electrode realized acceptable sensitivity and consistency for AM detection in pharmaceutical drugs.